Effect of Menstrual Cycle on Resting Energy Expenditure and Food Preferences - Yasemin Akdevelioğlu; Vildan Şimal Taşdemir; Mehlika Kabak; Edanur Berfu Uyduran; Büşra Atabilen (Advances in Women’s Studies)
Objective: It was aimed to evaluate the participants' resting energy expenditure, nutrient intake, food preferences, mindful eating and body composition in the follicular and luteal phase. Method: The study included 58 participants between the ages of 18-45 years, who had a stable menstrual cycle for a minimum of six months and normal body mass index (BMI). Participants were invited for resting energy expenditure, body weight and body composition analysis in both the follicular and luteal phases. Nutrient intake and food preferences were evaluated, and Mindful Eating Scale was applied in both phases. Results: Oxygen consumption (VO2) and resting energy expenditure (REE) were significantly higher in the luteal phase (p < .05). There was no significant difference between measurements of body weight and body composition analysis and nutrient intakes in both phases (p > .05). Although the preference for high-protein/low-fat foods, fatty foods and sugary foods tended to increase in the luteal phase, there was no significant difference between the phases (p > .05). Finally, it was shown that the mean score of Disinhibition subscale of Mindful Eating Scale was noticeably higher during the luteal period (p = .004). Conclusion: Changes in hormone levels during the menstrual cycle phases are an important factor to consider that may affect REE and impulsive eating. However, mindful eating strategies, dietary interventions and education programs are important in preventing the development of obesity and eating behavior disorders in predisposed individuals.